The Relative Influence of Age, Gender, Regional Differences and Their Relationship with Students' Numeracy Levels on Madrasah Competency Assessment in Indonesia - Kusaeri; Wahyudi, Noor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The numeracy level of students in Indonesia is a critical aspect in assessing educational competence, especially in madrasas with a distinctive religion- and science-based curriculum. This research was motivated by concerns regarding disparities in numeracy abilities that may be influenced by various demographic factors such as age, gender, and regional differences. This study aims to analyze students' numeracy skills based on age (10, 11, and 12 years), age relative to gender (male and female), and age relative to region (3T, district, and city). This data collection method uses descriptive correlational research to test the relationship between gender, geographical distribution in Indonesia, and the optimal age of students in numeracy. The data analysis method uses descriptive statistical analysis methods. The subjects in this study consisted of 297,257 Indonesian fifth-grade students participating in the Indonesian Madrasah Competency Assessment (IMCA. The results of linear regression analysis show that gender and regional status influence students' numeracy skills. The results of this research can be used as a basis for teachers to provide appropriate guidance to students in the learning process according to their age level. The implications of this research can help policymakers and schools design more targeted interventions to improve students' numeracy skills.